Policy Gaps in Postgraduate Supervision: An Evaluation of University Guidelines and Enforcement Using a Single Case Study Design - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background: Postgraduate supervision plays a critical role in shaping research quality and academic success. However, many universities experience a disconnect between formal supervision policies and their implementation, leading to inconsistent student experiences and supervision outcomes. At the selected university, concerns have emerged regarding unclear supervisory responsibilities, lack of student recourse mechanisms, and inconsistent enforcement of guidelines. This study seeks to evaluate the effectiveness of the university’s postgraduate supervision policies and identify key gaps in their enforcement. Methods: A qualitative single case study design was adopted, focusing on one South African university. Data was collected through document analysis of existing supervision policies and semi-structured interviews with academic supervisors (n=10), postgraduate students (n=12), and faculty postgraduate coordinators (n=3). Thematic analysis was used to explore the clarity, accessibility, and enforcement of policy documents, as well as stakeholder perceptions of institutional support structures. Results: The study revealed that although formal supervision policies exist, their enforcement is inconsistent across faculties. Many supervisors lacked awareness or formal training on policy provisions, and students reported dissatisfaction with the clarity of supervision expectations and lack of support when conflicts arise. While some departments showed good practices, the absence of a centralized enforcement and monitoring mechanism weakened overall policy effectiveness. Conclusion: The findings point to a significant policy-practice gap in postgraduate supervision at the institution. The lack of formal enforcement structures and inadequate communication of policy roles contribute to inequitable supervision experiences. Recommendations: The university should consider enhancing the visibility and accessibility of supervision policies, mandating training for all postgraduate supervisors, and establishing a monitoring unit within the postgraduate office. Introducing clear complaint and appeal processes and periodically reviewing policies with stakeholder input could improve accountability and consistency in postgraduate supervision.